Progression of Hepatic Adenoma to Carcinoma in the Setting of Hepatoportal Sclerosis in HIV Patient: Case Report and Review of the Literature - M. I. Montenovo; F. G. Jalikis; M. Yeh; J. D. Reyes (Case Reports in Hepatology)
We report a case of hepatic adenoma progression to carcinoma in the setting of hepatoportal sclerosis in an HIV+ patient and provide a review of the scarce literature regarding hepatoportal sclerosis in HIV patients. We describe the clinical presentation, diagnostic workup, and management. This is the first case report in the literature of progression of hepatic adenoma to carcinoma in hepatoportal sclerosis in an HIV patient. This case also highlights the broad differential diagnosis that should always be included in the study of any liver disease in this patient population, including the performance of invasive and aggressive tests to arrive at the final diagnosis.